Analysis of factors influencing contact dermatitis complaints among informal batik workers in Klaten Regency - Azhar, Eky Fadhildansyah; Setyaningsih, Yuliani; Lestantyo, Daru (Institute of Computer Science (IOCS), 2025)
The batik industry within the informal sector, particularly in Jarum Village, Bayat District, Klaten Regency, presents a high risk of contact dermatitis complaints due to exposure to synthetic chemical dyes used in the coloring process. This study aims to analyze the factors associated with contact dermatitis complaints among informal batik workers, focusing on individual characteristics (age, gender, length of employment, duration of exposure, personal hygiene, and use of Personal Protective Equipment/PPE) and environmental factors (workplace temperature and humidity). A quantitative method with an analytical observational approach and cross-sectional design was employed. A total of 146 respondents were selected through purposive sampling. The results indicate that age, duration of chemical exposure, personal hygiene, and PPE use are significantly associated with contact dermatitis complaints. These findings underscore the importance of preventive interventions through adequate PPE provision, hygiene education, and community-based occupational health monitoring, particularly within the informal batik industry.